INOVASI KEGIATAN KEAGAMAAN DI HIJABERS COMMUNITY MALANG - Rohmah Istikomah; Umi Sumbulah (STAI Ma'had Aly Al-Hikam Malang, 2023)
Hijab is now a new fashion trend among women. This stylish and modern hijab style phenomenon has attracted many Muslim women, especially the young ones. This fashionable hijab style was first introduced by a community known as the